1996
DOI: 10.1001/archpsyc.1996.01830020093011
|View full text |Cite
|
Sign up to set email alerts
|

Depressed Mood and the Incidence of Alzheimer's Disease in the Elderly Living in the Community

Abstract: Depressed mood moderately increased the risk of developing dementia, primarily Alzheimer's disease. Whether depressed mood is a very early manifestation of Alzheimer's disease, or increases susceptibility through another mechanism, remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
319
4
11

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(360 citation statements)
references
References 51 publications
23
319
4
11
Order By: Relevance
“…44-45 Multiple, non-mutually exclusive etiological causes have been proposed to explain this association between depression and dementia 46 and, generally, they all propose that the processes that play an etiological role in disrupting the neural circuitry underlying cognitive function and thus lead to dementia, also disrupt the neural network underlying mood. One brain area that overlaps between the mood and cognitive neural networks that may have special importance for this hypothesis is the hippocampus.…”
Section: Current Hypotheses For Biological Mechanisms Promoting Lldmentioning
confidence: 99%
“…44-45 Multiple, non-mutually exclusive etiological causes have been proposed to explain this association between depression and dementia 46 and, generally, they all propose that the processes that play an etiological role in disrupting the neural circuitry underlying cognitive function and thus lead to dementia, also disrupt the neural network underlying mood. One brain area that overlaps between the mood and cognitive neural networks that may have special importance for this hypothesis is the hippocampus.…”
Section: Current Hypotheses For Biological Mechanisms Promoting Lldmentioning
confidence: 99%
“…A case in point is depressive symptomatology. With relatively few exceptions, longitudinal studies have found higher level of depressive symptoms in old age to be associated with loss of cognition in the form of higher incidence of mild cognitive impairment (D. E. Barnes, Alexopoulos, Lopez, Williamson, & Yaffe, 2006: Geda et al, 2006 or dementia (Berger, Fratiglioni, Forsell, Winblad, & Bäckman, 1999;Devanand et al, 1996;Gatz, Tyas, St. John, & Montgomery, 2005;Modrego & Ferrández, 2004;Wilson, Barnes, et al, 2002;Wilson, Krueger, et al, 2007) or more rapid cognitive decline (Paterniti, Verdier-Tillefer, Dufouil, & Alperovitch, 2002;Sachs-Ericsson, Joiner, Plant, & Blazer, 2005;Wilson, Barnes, et al, 2002;Wilson, Mendes de Leon, Bennett, Bienias, & Evans, 2004;Yaffe et al, 1999). One interpretation of these data is that depressive symptoms are an early sign of the pathology associated with dementia.…”
Section: Factors Operating Through Other Mechanismsmentioning
confidence: 99%
“…MDD has been identified both as a risk factor and a prodrome of Alzheimer's disease (AD) in clinical and community samples (Reding et al, 1985;Kral and Emery, 1989;Kokmen et al, 1991;Jorm et al, 1991;Alexopoulos et al, 1993b;Speck et al, 1995;Devanand et al, 1996;Henderson et al, 1997;Steffens et al, 1997;Bassuk et al, 1998;Chen et al, 1999;Yaffe et al, 1999;Geerlings et al, 2000;Jorm, 2000;Lockwood et al, 2000;Visser et al, 2000;Jorm, 2001;Lockwood et al, 2002;Wilson et al, 2002;Green et al, 2003;Sweet et al, 2004;Cannon-Spoor et al, 2005;Gatz et al, 2006;Rapp et al, 2006;Steffens et al, 2006). Community based studies have identified clinical depression, including depressive symptoms as a risk factor for the subsequent development of dementia.…”
Section: Relationship Of Mdd To Admentioning
confidence: 99%
“…Community based studies have identified clinical depression, including depressive symptoms as a risk factor for the subsequent development of dementia. Devanand et al using a population based sample from northern Manhattan (NY, NY) found that after controlling for age, gender, education and initial level of cognition, depressed mood at baseline was associated with the development of AD with an odds ratio (OR) of 2.5 (Devanand et al, 1996). In the religious order study, > 600 elderly individuals were examined annually for as long as seven years (Wilson et al, 2002).…”
Section: Relationship Of Mdd To Admentioning
confidence: 99%